Adsorpsi Logam Kadmium dalam Limbah Cair Buatan Menggunakan Biosorben Kulit Pisang Mas (Musa acuminate colla) - Arifiyana, Djamilah; Wardani, Ratih Kusuma (Rekayasa, 2021)
Mas banana (Musa acuminata Colla) peel is a type of household waste as well as agricultural waste whose utilization still needs to be improved. In addition, among various types of heavy metals that are dangerous as contaminants in the environment, cadmium metal is a metal that is very dangerous to health even in very small amounts. Therefore, this study aims to not only utilize the waste of Mas banana peel (Musa acuminata Colla) as a biosorbent, but also to determine the optimum conditions needed to reduce cadmium metal which involves several test parameters, namely stirring time, pH and mass of biosorbent. Variations of stirring time used include 10, 20, 30, 35, and 45 minutes; variations in pH used include 1, 2, 3, 4, and 5, while variations in the mass of biosorbent used include 0.5; 1; 1.5; 2 and 2.5 grams. The results showed that the optimum conditions were obtained at a mixing time of 35 minutes, pH 5, and a mass of 2 grams of biosorbent with a reduction percentage value of 78.45%. This percentage indicates that Mas banana peel can be used as a natural adsorbent for cadmium metal. In addition, the results of the FT-IR analysis of the Mas banana peel biosorbent showed that Mas banana peel has a functional group that plays a role in the heavy metal adsorption process.